Influence of Time Dependence of Dynamic Laser Parameter on the Three Modes Random Laser Operation - Phu, Nguyen Van; Hoang, Dinh Van; Anh, Le Ngoc (Communications in Physics, 2013)
In this report we demonstrate the transformation of the photon density curves in operation of a three modes random laser when the gain coefficients of modes depending on time.Supposing gain coefficients having Gaussian profile and using Matlab language, we have solved the basic equations describing the operation of a three modes random laser. The received results give us more real knowledge about the appearance of modes in random laser.